INTERRELATIONS BETWEEN ECLIPSING BINARY SYSTEMS OF VARIOUS TYPES AT THE STAGE OF THE FIRST MASS EXCHANGE - Karetnikov, V. G. (Одеські астрономічні публікації, 2017)
Topics of the empirical study of the evolutionary directions of the eclipsing binary stars of different types are reviewed. It was shown that close binary systems at the first stage of the mass exchange may be distingui- shed into 3 evolutionary groups, the members of which may evolve from one group to another. This suggestion is justified by the analysis of the dependencies of the main characteristics of the stellar components in binaries and by the location of them at the proposed diagram of the degrees of filling the Roche Lobe.